Determinan Pengungkapan Modal Intelektual Berdasarkan Variable Non Keuangan pada Perusahaan Manufaktur di Indonesia - Tri Hardiyanti, Nidia (Journal of Comprehensive Science, 2024)
The purpose of the research are to analyze the influence of family ownership, foreign ownership,audit committees, and independent commissioners of intellectual capital disclosure. The population in this research are the manufacturing companies listed in Indonesia Stock Exchange for 2015-2017. The sampling technique is a purposive sampling method which result from 63 samples. Data are collected using secondary data from manufacturing companies listed in Indonesia stock Exchange. Data analysis was performed using descriptive statistic analysis and multiple linear regression analysis. The result of this study shows that the following variable family ownership, foreign ownership does not significant affect toward intellectual capital disclosure, while variable audit committess and independent commissioners significantly effect toward intellectual capital disclosure.